IMPLEMENTASI PERATURAN MENTERI KESEHATAN REPUBLIK INDONESIA NOMOR 15 TAHUN 2013 TENTANG PENGADAAN FASILITAS RUANG ASI DI PUSAT PERBELANJAAN KOTA SAMARINDA - Yudha Yudha (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTION             This study aims to determine the implementation of Regulation of the Minister of Health of the Republic of Indonesia No. 15 of 2013 on Procedures for the Provision of Special Breastfeeding Facility and / or Breast Milk at shopping centers in the city of Samarinda and how efforts, actions and constraints Local Government of Samarinda city and related agencies in the implementation of Regulation Minister of Health of the Republic of Indonesia Number 15 Year 2013 on Procedures for the Provision of Special Breastfeeding Facility and / or Breast Milk.       This research was conducted by interview and observation at two big shopping center of Samarinda city, and interview in three related institutions namely Samarinda City Office, Samarinda City Health Office, and Samarinda City Manpower Office.       Based on the results of the author's discussion, it can be concluded as follows: that in two shopping centers studied only one apply the rule. Then still less optimal efforts made by the Government of Samarinda related sociasliasi Regulation of the Minister of Health of the Republic of Indonesia No. 15 of 2013 on Procedures for the Provision of Special Facilities Breastfeeding and / or milking this is due to constraints in funding related discourses that support the availability of breast milk khsuus room in all so that the Regulation of the Minister of Health of the Republic of Indonesia Number 15 of 2013 on Procedures for the Provision of Special Facilities Breastfeeding and / or milking milk can work well. The action is deemed to be insufficiently clear that the need for PPNS officers to implement the Regulation of the Minister of Health of the Republic of Indonesia Number 15 of 2013 on Procedures for the Provision of Special Breastfeeding Facility and / or milking milk can run smoothly. The need for solutions to efforts made by relevant agencies to run well and also need future legal action on the availability of breastfeeding room. Keywords: Female, female labor, breast milk, and Implementation of  Minister of Health Regulation No. 15 of 2013